Use of Chitosan to Prevent Aeromonas hydrophila Infection on Catfish Clarias sp. - . Sukenda; L. Jamal; D. Wahjuningrum; A. Hasan (Jurnal Akuakultur Indonesia)
Immunostimulation effect of chitosan against motile aeromonas septicemia caused by Aeromonas hydrophila were examined in catfish (Clarias sp.). Experimental fish were injected with 2, 4 and 6 μg/g fish of chitosan.  All fish were subsequently challenged by 105 CFU/ml of live A. hydrophila by injection method.  Negative control injected with PBS and positive control injected with only A. hydrophila were included in the experiment. Results showed that total count of eritrocyte, leucocyte,  level of hematocrite, haemoglobin and phagocytic index higher at fish injected with chitosan previously compared with control as well as lymphocyte, neutrophile, monocyte, and trombocyte.  Either survival rate or growth  of fish injected with chitosan were found to increase in accordance with dose of chitosan.